Multilayer electronic assembly and method of manufacturing the same
Patent Information
- Application Number
- CN202610435057.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-03
- Filing Date
- 2026-04-03
- Publication Date
- 2026-10-16
AI Technical Summary
然而,随着介电层和内电极的厚度减小,施加到介电层和内电极中的每层的电场强度变得相对强,因此可能存在MLCC的高温可靠性和防潮可靠性劣化的问题
[0009] One effect of this disclosure is to improve the reliability of multilayer electronic components.
Smart Images

Figure CN122930732A_ABST
Abstract
Description
[0001] This application claims the benefit of priority to Korean Patent Application No. 10-2025-0043310, filed on April 3, 2025, with the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] This disclosure relates to a multilayer electronic component and a method for manufacturing the multilayer electronic component. Background Technology
[0003] Multilayer ceramic capacitors (MLCCs, a type of multilayer electronic component) are chip capacitors mounted on printed circuit boards in various electronic products, such as image display devices (such as liquid crystal displays (LCDs) and plasma display panels (PDPs)), computers, smartphones, and mobile phones, to charge or discharge them. MLCCs are used as components in various electronic devices due to their small size, high capacitance, and ease of installation.
[0004] To miniaturize MLCCs, the dielectric layer and internal electrodes should be made thinner. However, as the thickness of the dielectric layer and internal electrodes decreases, the electric field strength applied to each layer of the dielectric layer and internal electrodes becomes relatively strong, which may lead to a deterioration in the high-temperature reliability and moisture resistance reliability of MLCCs. Summary of the Invention
[0005] One aspect of this disclosure is to provide a multilayer electronic component with excellent reliability.
[0006] However, the aspects of this disclosure are not limited to the foregoing and can be more readily understood in the process of describing specific embodiments of this disclosure.
[0007] A multilayer electronic component according to an example embodiment of the present disclosure may include: a body including a dielectric layer and inner electrodes alternately disposed with the dielectric layer, the dielectric layer including Ba, Ti and Ge; and an outer electrode disposed on the body, wherein the dielectric layer includes a plurality of dielectric grains and grain boundaries disposed between adjacent dielectric grains, and the average Ge content relative to Ti at the grain boundaries may be greater than or equal to 0.2 at% and less than or equal to 4.5 at%.
[0008] A method for manufacturing the above-described multilayer electronic component according to an example embodiment of the present disclosure may include: coating a slurry onto a film to form a plurality of ceramic green sheets; coating a first paste onto each of the plurality of ceramic green sheets; stacking the plurality of ceramic green sheets to form a laminate; sintering the laminate to form the body; and coating a second paste onto the body to form the external electrode, wherein the first paste or the slurry may include GeO2.
[0009] One effect of this disclosure is to improve the reliability of multilayer electronic components. Attached Figure Description
[0010] The above and other aspects, features and advantages of this disclosure will become clearer from the following detailed embodiments, taken in conjunction with the accompanying drawings, in which: Figure 1 This is a perspective view schematically illustrating a multilayer electronic assembly according to an exemplary embodiment of the present disclosure; Figure 2 It schematically shows along Figure 1 A cross-sectional view of the section intercepted by line I-I'; Figure 3 It schematically shows along Figure 1 A cross-sectional view of the section intercepted by line II-II'; Figure 4 It is shown schematically. Figure 1 An exploded 3D view of the main body; Figure 5 It is shown schematically. Figure 2 A magnified view of region K; Figure 6 Images of the dielectric layer and internal electrodes were obtained using a scanning transmission electron microscope (STEM); and Figure 7 These images were obtained by using a scanning transmission electron microscope (STEM) to photograph the grain boundaries of the dielectric layer. Detailed Implementation
[0011] In the following description, exemplary embodiments of the present disclosure will be illustrated with reference to the accompanying drawings. However, exemplary embodiments of the present disclosure may be exemplified in many different forms and should not be construed as limited to the specific embodiments set forth herein. Furthermore, the exemplary embodiments disclosed herein are provided to better explain the present disclosure to those skilled in the art. Therefore, in the drawings, the shape and size of elements may be exaggerated for clarity, and the same reference numerals will always be used to denote the same elements.
[0012] Furthermore, for the sake of clarity in the accompanying drawings, details irrelevant to the description have been omitted, and the disclosure is not limited thereto because the dimensions (e.g., thickness) of each component shown in the drawings are arbitrarily illustrated for ease of description. Additionally, the same reference numerals are used to describe components having the same function within the same conceptual scope. Throughout the specification, unless otherwise stated, when a part “includes” or “comprises” a component, this indicates that other components are not excluded and may be further included.
[0013] In the accompanying drawings, the X direction can be defined as the thickness direction, the Y direction can be defined as the length direction, and the Z direction can be defined as the width direction. In this disclosure, "thickness" can refer to a dimension in the thickness direction, "length" can refer to a dimension in the length direction, and "width" can refer to a dimension in the width direction. Multilayer electronic components
[0014] Figure 1 This is a perspective view schematically illustrating a multilayer electronic assembly according to an exemplary embodiment of the present disclosure.
[0015] Figure 2 It schematically shows along Figure 1 A cross-sectional view of the section intercepted by line I-I'.
[0016] Figure 3 It schematically shows along Figure 1 A cross-sectional view of the section cut by line II-II'.
[0017] Figure 4 It is shown schematically. Figure 1 An exploded 3D view of the main body.
[0018] Figure 5 It is shown schematically. Figure 2 A magnified view of region K.
[0019] In the following text, reference will be made to Figures 1 to 5 A multilayer electronic assembly 100 according to an exemplary embodiment of the present disclosure is described in detail. Furthermore, a multilayer ceramic capacitor will be described as an example of a multilayer electronic assembly. However, the present disclosure is not limited thereto and can be applied to various multilayer electronic assemblies, such as inductors, piezoelectric elements, varistors, or thermistors.
[0020] The length of the multilayer electronic component 100 may be greater than both its width and thickness, but this disclosure is not limited thereto. For example, the length of the multilayer electronic component 100 may be less than its width. The width of the multilayer electronic component 100 may be less than or greater than its thickness, depending on the target specifications or characteristics of the multilayer electronic component 100.
[0021] A multilayer electronic component 100 according to an example embodiment of the present disclosure may include a body 110 and external electrodes 131 and 132 disposed on the body 110.
[0022] Although there are no particular restrictions on the specific shape of the main body 110, however... Figure 1As shown, the body 110 may be formed in a hexahedral shape or a shape similar to a hexahedron. Due to the shrinkage of the ceramic powder particles included in the body 110 during the sintering process, or due to the polishing process of the corners of the body 110, the body 110 may not have a perfect right hexahedral shape, but may have a generally hexahedral shape.
[0023] The main body 110 may have a first surface 1 and a second surface 2 that are opposite to each other in the thickness direction, a third surface 3 and a fourth surface 4 that are connected to the first surface 1 and the second surface 2 and are opposite to each other in the length direction, and a fifth surface 5 and a sixth surface 6 that are connected to the first surface 1, the second surface 2, the third surface 3 and the fourth surface 4 and are opposite to each other in the width direction.
[0024] The body 110 may include dielectric layers 111 and internal electrodes 121 and 122 alternately disposed with the dielectric layers 111. The plurality of dielectric layers 111 forming the body 110 are in a sintered state, and adjacent dielectric layers 111 may be integrated, making it difficult to identify the boundaries between them without using a scanning electron microscope (SEM).
[0025] The main body 110 may include a capacitor forming portion Ac, which forms a capacitor by including an alternately arranged first inner electrode 121 and a second inner electrode 122, with a dielectric layer 111 positioned between the first inner electrode 121 and the second inner electrode 122. The inner electrodes 121 and 122 may be stacked in either the thickness direction or the width direction. This disclosure will be described with reference to an example embodiment where the stacking direction of the inner electrodes 121 and 122 is the thickness direction.
[0026] The first inner electrode 121 may be spaced apart from the fourth surface 4 and may be connected to the first outer electrode 131 located on the third surface 3. The second inner electrode 122 may be spaced apart from the third surface 3 and may be connected to the second outer electrode 132 located on the fourth surface 4.
[0027] The main body 110 may include cover portions 112 and 113 and edge portions 114 and 115. Cover portions 112 and 113 are disposed on opposing surfaces of the capacitor forming portion Ac in the thickness direction, and edge portions 114 and 115 are disposed on opposing surfaces of the capacitor forming portion Ac in the width direction. Cover portions 112 and 113 and edge portions 114 and 115 do not include internal electrodes and may have the same material as the dielectric layer 111.
[0028] The external electrodes 131 and 132 may include: a first external electrode 131 disposed on the third surface 3 and extending to a portion of the first surface 1, a portion of the second surface 2, a portion of the fifth surface 5 and a portion of the sixth surface 6; and a second external electrode 132 disposed on the fourth surface 4 and extending to a portion of the first surface 1, a portion of the second surface 2, a portion of the fifth surface 5 and a portion of the sixth surface 6.
[0029] There are no particular limitations on the type or shape of the outer electrodes 131 and 132, and the outer electrodes 131 and 132 may have a multilayer structure. For example, the outer electrodes 131 and 132 may include a base electrode layer in contact with the inner electrodes 121 and 122, and a plating layer disposed on the base electrode layer.
[0030] The base electrode layer can be a sintered electrode layer comprising a metal and a glass. The metal included in the sintered electrode layer may include, for example, Cu, Ni, Pd, Pt, Au, Ag, Pb and / or alloys thereof. The glass included in the sintered electrode layer may include, for example, one or more oxides of Ba, Ca, Zn, Al, B and Si.
[0031] The substrate electrode layer may consist of only a sintered electrode layer, but this disclosure is not limited thereto. The substrate electrode layer may include a sintered electrode layer and a resin electrode layer. The sintered electrode layer includes metal and glass, and the resin electrode layer is disposed on the sintered electrode layer and includes metal particles and resin.
[0032] The metal particles included in the resin electrode layer may include at least one of spherical particles and plate-like particles. The metal particles included in the resin electrode layer may include, for example, Cu, Ni, Pd, Pt, Au, Ag, Pb, Sn, and / or alloys thereof. The resin included in the resin electrode layer may include, for example, one or more of epoxy resin, acrylic resin, and ethyl cellulose resin.
[0033] The coating may include, for example, Ni, Sn, Pd and / or alloys thereof, and may consist of multiple layers. The coating may be, for example, a Ni coating or a Sn coating, or may have Ni and Sn coatings formed sequentially. The coating may include multiple Ni coatings and / or multiple Sn coatings.
[0034] Figure 1 and Figure 2 The diagram shows a multilayer electronic assembly 100 with two external electrodes 131 and 132. However, this disclosure is not limited thereto, and the number and / or shape of the external electrodes 131 and 132 may vary depending on the shape of the internal electrodes 121 and 122 or for other purposes.
[0035] The dielectric layer 111 may include Ba and Ti. For example, the dielectric layer 111 may include a perovskite-type compound represented by ABO₃ as a main component. A may include Ba, and B may include Ti. The perovskite-type compound may include, for example, BaTiO₃, (Ba 1-x Ca x )TiO₃ (0<x<1), Ba(Ti 1-y Ca y )O₃ (0<y<1), (Ba 1-x Ca x )(Ti 1-y Zr y )O₃ (0<x<1, 0<y<1) and Ba(Ti 1-y Zr y )O₃ (0<y<1), one or more thereof. In the present disclosure, the main component may refer to a component whose proportion is relatively larger than that of other components, and may refer to a component having a content of 50 wt% or more or 50 at% or more based on the entire composition or the entire dielectric layer.
[0036] The dielectric layer 111 may include a plurality of dielectric crystal grains 111a and grain boundaries 111b disposed between adjacent dielectric crystal grains. That is, the grain boundary 111b may refer to a boundary between adjacent dielectric crystal grains, and the dielectric crystal grain 111a may be surrounded by a plurality of grain boundaries 111b. The boundary between the dielectric crystal grain 111a and the grain boundary 111b may be defined in a manner such as by binarizing an image captured by a transmission electron microscope to distinguish portions having different brightness levels.
[0037] As the thicknesses of the dielectric layer 111 and the inner electrodes 121 and 122 of the multilayer electronic component 100 decrease, the electric field strength applied to each of the dielectric layer 111 and the inner electrodes 121 and 122 becomes relatively strong, which may reduce the reliability of the multilayer electronic component 100. In addition, it is known that a main component of insulation resistance (IR) characterizing dielectric reliability is grain boundary resistance caused by a Schottky-type energy barrier present at the grain boundaries.
[0038] The dielectric layer 111 may include Ge. When Ge is distributed at the grain boundaries 111b, Ge may function as a barrier that increases the grain boundary resistance, thereby improving the reliability of the multilayer electronic component 100. However, when Ge is excessively distributed at the grain boundaries 111b, local electric field concentration may be caused due to an irregular increase in the grain boundary resistance, or grain growth of the dielectric crystal grains 111a may be excessively suppressed to deteriorate the reliability of the multilayer electronic component 100. Therefore, in order to improve the reliability of the multilayer electronic component 100, it is necessary to appropriately control the Ge content at the grain boundaries 111b.
[0039] According to an exemplary embodiment of this disclosure, the average Ge content C at grain boundary 111b relative to Ti is... GB It can be greater than or equal to 0.2at% and less than or equal to 4.5at%. When C GB When the above numerical range is met, the reliability of the multilayer electronic component 100 can be effectively improved.
[0040] The average Ge content C relative to Ti at grain boundary 111b was obtained. GB An example of the method is as follows. First, a cross-section along the length-thickness direction (hereinafter referred to as the measurement section) is exposed by grinding to the center of the width direction of the multilayer electronic assembly 100. Then, a thin film sample for observation by scanning transmission electron microscopy (STEM) is prepared by focusing ion beam (FIB) microsampling, and the thin film sample is subjected to Ar ion grinding to remove the damaged layer on the surface of the thin film sample. Then, an electron beam probe with a diameter of about 0.2 nm is used to analyze a point at the grain boundary. In this case, only the grain boundary 111b perpendicular to the electron beam is analyzed. The composition of the grain boundary 111b can be analyzed using an energy-dispersive X-ray analyzer (EDS) mounted on the scanning transmission electron microscope (STEM), thereby measuring the content of Ge (at%) and Ti (at%). Here, the content (at%) refers to the content expressed as an atomic percentage. The Ge content at the grain boundary 111b relative to Ti can be obtained by dividing the measured Ge content (at%) by the Ti content (at%). Additionally, by performing content measurements at 10 or more grain boundaries 111b and then averaging the measurements, the average Ge content (C) at the grain boundaries 111b relative to Ti can be obtained. GB Even if not described in this disclosure, other methods and / or tools that are understood by one of ordinary skill in the art may be used.
[0041] In an example embodiment, the average Ge content (at%) relative to Ti within the plurality of dielectric grains 111a may be less than the average Ge content (at%) relative to Ti at the grain boundaries 111b. Ge can be more distributed at the grain boundaries 111b rather than dissolved within the dielectric grains 111a, thereby increasing the insulation resistance of the dielectric layer 111. The Ge content relative to Ti within the plurality of dielectric grains 111a can be measured by dividing the Ge content (at%) measured via EDS by the Ti content (at%) measured via EDS. Furthermore, the average Ge content C relative to Ti within the plurality of dielectric grains 111a can be obtained by performing content measurements on 10 or more dielectric grains 111a and then averaging the measurements. DG Even if not described in this disclosure, other methods and / or tools that are understood by one of ordinary skill in the art may be used.
[0042] In an example embodiment, inner electrodes 121 and 122 may comprise a Ni-Ge alloy. When Ni and Ge are sintered together in a reducing atmosphere, the Ni-Ge alloy can be uniformly formed within the inner electrodes 121 and 122. The Ni-Ge alloy reduces the grain boundary energy and surface tension of Ni, thereby improving the smoothness and connectivity of the inner electrodes 121 and 122. When the smoothness of the inner electrodes 121 and 122 is improved, the electric field intensity applied to the dielectric layer 111 can be effectively dispersed even when the thickness of the dielectric layer 111 is reduced.
[0043] Furthermore, by alloying the quasi-metal Ge with Ni, the insulation at the interface between the dielectric layer 111 and the internal electrodes 121 and 122 can be improved, thereby improving the reliability of the multilayer electronic component 100. In addition, since the sintering rate of Ni is slowed down during the Ni-Ge alloying process, the connectivity of the internal electrodes can be further improved, thereby enabling the realization of a multilayer electronic component 100 with higher capacity.
[0044] In the example embodiment, the average Ge content C relative to Ni in the internal electrodes 121 and 122 IE The capacitance can be greater than or equal to 0.32 at% and less than or equal to 6.3 at%. When the above numerical range is met, the capacitance and reliability of the multilayer electronic component 100 can be improved more effectively. Furthermore, Ge included in the inner electrodes 121 and 122 can diffuse into the grain boundaries 111b of the dielectric layer 111 during the sintering process. Therefore, when C... IE When the above numerical range is met, C can be controlled more effectively. GB .
[0045] In addition to the Ni-Ge alloy, the internal electrodes 121 and 122 may also include one or more conductive metals selected from the group consisting of Cu, Ag, Pd, Au, Al and Sn, but this disclosure is not limited thereto.
[0046] The Ge content (at%) relative to Ni in the inner electrodes 121 and 122 can be measured by dividing the Ge content measured using STEM-EDS at a point inside the inner electrodes 121 and 122 by the Ni content measured using STEM-EDS at that point inside the inner electrodes 121 and 122. Furthermore, content measurements can be performed at three or more arbitrary points within one inner electrode 121 or 122 and / or at three or more inner electrodes 121 and 122, and the measurements can then be averaged to obtain the average Ge content C relative to Ni in the inner electrodes. IE Even if not described in this disclosure, other methods and / or tools that are understood by one of ordinary skill in the art may be used.
[0047] The secondary components that may be included in dielectric layer 111 will be described in detail below. The contents of the secondary components are described based on the molar number of elements and can be calculated by converting the amount of oxides or carbonates added as additives prior to sintering. The contents of the secondary components can be measured using various methods such as SEM-EDS, TEM-EDS, and STEM-EDS.
[0048] a) First sub-component
[0049] The dielectric layer 111 may further include a first secondary component comprising one or more of Y, Dy, Tb, Ho, Er, Gd, Ce, Nd, Sm, Tm, La, and Yb. The first secondary component can improve the high-temperature accelerated lifespan of the multilayer electronic component 100.
[0050] The content of the first sub-component relative to 100 mol of Ti can be greater than or equal to 2.5 mol and less than or equal to 8.0 mol. When the content of the first sub-component relative to 100 mol of Ti is less than 2.5 mol or greater than 8.0 mol, the room temperature dielectric constant and / or insulation resistance characteristics may deteriorate.
[0051] The dielectric layer 111 may include, for example, Dy. In an example embodiment, the average Dy content relative to Ti at the grain boundary 111b may be greater than or equal to 2.0 at% and less than or equal to 5.0 at%. When the above numerical range is met, the reliability of the multilayer electronic component 100 can be improved more effectively.
[0052] b) Second sub-component
[0053] The dielectric layer 111 may also include a second component comprising one or more of Mn, V, Cr, Fe, Co, Ni, Cu, and Zn. The second component can be used to reduce the sintering temperature and improve the dielectric properties and high-temperature accelerated life performance of the multilayer electronic component 100.
[0054] The content of the second sub-component relative to 100 moles of Ti can be greater than or equal to 0.2 mol and less than or equal to 1.4 mol. When the content of the second sub-component relative to 100 moles of Ti is less than 0.2 mol, there is a concern that the high-temperature accelerated lifetime may deteriorate, and when the content of the second sub-component relative to 100 moles of Ti is greater than 1.4 mol, there is a concern that the dielectric constant may deteriorate.
[0055] c) Third sub-component
[0056] The dielectric layer 111 may also include a third sub-component containing magnesium. The third sub-component can impart resistance to reduction and can increase the RC value, which is the product of the resistance and capacitance values.
[0057] The content of Ti in the third sub-component based on 100 mol can be greater than 0 mol and less than or equal to 2.0 mol. When the content of Ti in the third sub-component based on 100 mol is greater than 2.0 mol, there is a concern that the temperature coefficient of capacitance (TCC) may not meet the X7R characteristics.
[0058] In the example embodiment, the average Mg content relative to Ti at the grain boundary 111b can be greater than or equal to 0.2 at% and less than or equal to 1.0 at%. When the above numerical range is met, the reliability of the multilayer electronic component 100 can be improved more effectively.
[0059] d) Fourth sub-component
[0060] The dielectric layer 111 may also include a fourth sub-component comprising at least one of Si and Al. Similar to Ge, when Si and / or Al are distributed at the grain boundaries 111b, Si and / or Al can act as a barrier to increase the grain boundary resistance, thereby improving the reliability of the multilayer electronic component 100.
[0061] Specifically, due to the high chemical stability of Si and / or Al, Si and / or Al can be relatively uniformly distributed at the grain boundaries 111b, and can also be used to maintain the uniform size of the dielectric grains 111a.
[0062] Therefore, the average Si content (at%) relative to Ti at grain boundary 111b can be greater than the average Ge content (at%) relative to Ti at grain boundary 111b, but this disclosure is not limited thereto.
[0063] Similarly, the average Al content (at%) relative to Ti at grain boundary 111b can be greater than the average Ge content (at%) relative to Ti at grain boundary 111b, but this disclosure is not limited thereto.
[0064] For example, the average Si content (at%) relative to Ti at grain boundary 111b may be greater than or equal to 7.0 at% and less than or equal to 9.0 at%, but this disclosure is not limited thereto. For example, the average Al content (at%) relative to Ti at grain boundary 111b may be greater than or equal to 8.0 at% and less than or equal to 10.0 at%, but this disclosure is not limited thereto.
[0065] Besides using STEM-EDS to measure Dy (at%), Mg (at%), Si (at%), and Al (at%) instead of Ge (at%), the method for obtaining the average Dy content, average Mg content, average Si content, and average Al content relative to Ti at grain boundary 111b can be compared with the method for obtaining C. GBThe method is the same. Other methods and / or tools, as understood by one of ordinary skill in the art, may be used even if not described in this disclosure.
[0066] The average size of the dielectric grain 111a is not particularly limited, but may be greater than or equal to 120 nm and less than or equal to 200 nm. For example, the average size of the dielectric grain 111a may be measured from an image obtained by taking a measurement cross-section using a scanning electron microscope (SEM). Other methods and / or tools that are understood by those skilled in the art may be used, even if not described in this disclosure.
[0067] There is no particular limitation on the average thickness td of the dielectric layer 111. For example, the average thickness td of the dielectric layer 111 can be greater than or equal to 0.05 μm and less than or equal to 2.5 μm, greater than or equal to 0.05 μm and less than or equal to 1.0 μm, greater than or equal to 0.05 μm and less than or equal to 0.5 μm, or greater than or equal to 0.05 μm and less than or equal to 0.4 μm.
[0068] There is no particular limitation on the average thickness te of the inner electrodes 121 and 122. For example, the average thickness te of the inner electrodes 121 and 122 may be greater than or equal to 0.05 μm and less than or equal to 1.0 μm, greater than or equal to 0.05 μm and less than or equal to 0.5 μm, or greater than or equal to 0.05 μm and less than or equal to 0.4 μm.
[0069] The average thickness td of dielectric layer 111 and the average thickness te of inner electrodes 121 and 122 can be measured by scanning the measurement cross-section at 10,000x magnification using a scanning electron microscope (SEM). More specifically, the average thickness td of dielectric layer 111 can be measured by measuring the thickness at multiple points (e.g., five points spaced apart from each other at equal intervals along the length direction) on dielectric layer 111 and then taking the average. Similarly, the average thickness te of inner electrodes 121 and 122 can be measured by measuring the thickness at multiple points (e.g., five points spaced apart from each other at equal intervals along the length direction) on inner electrode 121 or 122 and then taking the average. Five equally spaced points can be specified in the capacitor forming section Ac. Furthermore, the average thickness td of dielectric layer 111 can be further generalized by performing such thickness measurements on ten dielectric layers 111 and then taking their average, and the average thickness te of inner electrodes 121 and 122 can be further generalized by performing such thickness measurements on ten inner electrodes 121 and 122 and then taking their average.
[0070] The average thickness tc of the covering portions 112 and 113 is not particularly limited. For example, the average thickness of the covering portions 112 and 113 may be 5 μm or more and 100 μm or less, 5 μm or more and 50 μm or less, 5 μm or more and 30 μm or less, or 5 μm or more and 20 μm or less. Here, the average thickness tc of the covering portions 112 and 113 refers to the average thickness of each of the first covering portion 112 and the second covering portion 113, respectively. The average thickness tc of the covering portions 112 and 113 may be a value obtained by averaging the thicknesses measured at five points of one covering portion 112 or 113 in the measurement cross section that are spaced apart from each other at equal intervals in the length direction.
[0071] Hereinafter, an example of a method for forming the multilayer electronic component 100 will be described. However, the method for manufacturing the multilayer electronic component 100 is not limited thereto.
[0072] First, ceramic powder particles for forming the dielectric layer 111 are prepared. The ceramic powder particles may be perovskite-type compound powder particles represented by ABO3. The perovskite-type compound powder particles may include, for example, BaTiO3, (Ba 1-x Ca x )TiO3 (0<x<1), Ba(Ti 1-y Ca y )O3 (0<y<1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0<x<1, 0<y<1) and Ba(Ti 1-y Zr y )O3 (0<y<1) of one or more. The BaTiO3 powder particles can be synthesized, for example, by reacting a titanium raw material (such as titanium dioxide) and a barium raw material (such as barium carbonate). Methods for synthesizing the ceramic powder particles include, for example, a solid-state method, a sol-gel method, and a hydrothermal synthesis method, but the present disclosure is not limited thereto. Next, the prepared ceramic powder particles are dried and ground, then mixed with an organic solvent (such as ethanol), a binder (such as polyvinyl butyral), and the first to fourth subcomponent powder particles to prepare a ceramic slurry, and then the ceramic slurry is applied onto a carrier film and dried to form a ceramic green sheet.
[0073] Next, an internal electrode conductive paste, comprising metal powder particles, binder, organic solvent, etc., is printed onto a ceramic green sheet to a predetermined thickness using screen printing or gravure printing to form an internal electrode pattern. The metal powder particles may include, for example, nickel (Ni) powder particles. Furthermore, the metal powder particles may also include one or more of copper (Cu), silver (Ag), lead (Pd), gold (Au), aluminum (Al), and tin (Sn) powder particles.
[0074] The internal electrode conductive paste may include GeO2 powder particles. There is no particular limitation on the content of GeO2 powder particles in the internal electrode conductive paste, but the content of GeO2 powder particles relative to nickel (Ni) in the internal electrode conductive paste may be greater than or equal to 0.5 wt% and less than or equal to 10 wt%.
[0075] Then, ceramic green sheets with internal electrode patterns printed on them are peeled off from the carrier film, and a predetermined number of ceramic green sheets with internal electrode patterns printed on them are stacked and pressed to form a ceramic laminate. A predetermined number of ceramic green sheets without internal electrode patterns can be stacked in the upper and lower parts of the ceramic laminate to form cover portions 112 and 113 after sintering. Then, the ceramic laminate is cut to a predetermined sheet size to form a unit ceramic laminate, and the unit ceramic laminate is sintered to form a body 110 including a dielectric layer 111 and internal electrodes 121 and 122. For example, sintering can be performed for 1 to 3 hours in an atmosphere of 1.0% H2 / 99.0% N2 (vol%) to 3.5% H2 / 96.5% N2 (vol%) (H2O / H2 / N2) at a temperature greater than or equal to 1000°C and less than or equal to 1400°C.
[0076] During the sintering process, Ni and Ge are alloyed, so the inner electrodes 121 and 122 may comprise a Ni-Ge alloy. Furthermore, Ge included in the conductive paste of the inner electrodes can diffuse into the dielectric layer 111 during the sintering process, and the diffused Ge can be distributed at the grain boundaries 111b, thereby controlling the average Ge content relative to Ti at the grain boundaries. However, this disclosure is not limited thereto; the average Ge content relative to Ti at the grain boundaries can also be controlled by individually adding GeO2 powder particles to the ceramic slurry used to form the dielectric layer 111.
[0077] Next, external electrodes 131 and 132 are formed. For example, when the base electrode layer includes a sintered electrode layer, the body 110 can be impregnated with an external electrode conductive paste comprising metal powder particles, glass frit, binder and organic solvent, and then the external electrode conductive paste can be sintered at a temperature of 500°C to 900°C to form a sintered electrode layer.
[0078] For example, when the base electrode layer includes a resin electrode layer, the substrate can be impregnated into a conductive resin composition comprising metal powder particles, resin, binder and organic solvent, and then thermo-cured at a temperature of 250°C to 550°C to form the resin electrode layer.
[0079] Alternatively, electroplating and / or electroless plating can be performed to form a coating on the substrate electrode layer. (Test example)
[0080] The present disclosure will be described in more detail below with test examples. However, the test examples below are intended to aid in a concrete understanding of the present disclosure and are not intended to limit its scope.
[0081] Using the above method, sample sheets of size 0603 (length: about 0.6 mm; width: about 0.3 mm; thickness: about 0.3 mm) were manufactured, and sample sheets of the inventive example and comparative example were manufactured by adjusting the content of GeO2 relative to Ni in the conductive paste of the internal electrode from 0 wt% to 12 wt%.
[0082] Then, the length-thickness cross-section was exposed by polishing the center of each sample sheet in the width direction. Thin film samples for scanning transmission electron microscopy (STEM) observation were then prepared by FIB microsampling. The surface damage layer was then removed by Ar ion polishing, and STEM-EDS analysis was performed under the conditions of an accelerating voltage of 200 kV and a probe diameter of 0.2 nm. Figure 6 The images were obtained by using a scanning transmission electron microscope (STEM) to photograph the dielectric layer and the inner electrode. Figure 7 This is an image of the grain boundary 111b of the dielectric layer obtained using STEM.
[0083] Then, the Ge content (at%) relative to Ti was measured at 10 grain boundaries perpendicular to the electron beam. This content measurement was performed on 20 sample pieces for each comparative example and the invention example, and the average value was calculated to obtain the average Ge content C at the grain boundaries relative to Ti. GB .
[0084] Similarly, the Ge content relative to Ni was measured at three arbitrary points within the internal electrode using STEM-EDS, and such content measurements were performed on 20 sample pieces for each comparative example and inventive example. The average value was calculated to obtain the average Ge content C relative to Ni in the internal electrode. IE .
[0085] Then, high-temperature accelerated life evaluation was performed on 40 sample pieces from each comparative example and each inventive example at 125°C and 9.5V, and the mean time to failure (MTTF) value was measured. In this case, the time when the insulation resistance is less than or equal to 10kΩ was used as the MTTF value, and the MTTF value of Comparative Example 1 was used as Reference Value 1, and the MTTF values of the other comparative examples and inventive examples were listed in the form of relative values based on the reference value.
[0086] [Table 1]
[0087] Referring to Table 1, for C GB For Comparative Examples 1 and 2, with values less than 0.2 at%, it was confirmed that the MTTF of the sample pieces was not improved. However, when C... GB When C is greater than or equal to 0.2 at%, MTTF is significantly improved. However, for Comparative Example 3, it can be confirmed that when C... GB When the content exceeds 4.5 at%, the presence of excessive Ge within the grain boundaries leads to a decrease in MTTF.
[0088] Therefore, as in Examples 1 to 5 of the Invention, it can be confirmed that when the average Ge content C at the grain boundary relative to Ti... GB When the reliability of multilayer electronic components is greater than or equal to 0.2at% and less than or equal to 4.5at%, the reliability is significantly improved.
[0089] This disclosure is not limited to the above-described exemplary embodiments and drawings, but is defined by the appended claims. Therefore, those skilled in the art can make various substitutions, modifications, or alterations without departing from the scope of this disclosure as defined by the appended claims, and such substitutions, modifications, or alterations should be construed as being included within the scope of this disclosure.
[0090] Furthermore, the term "example embodiment" as used in this disclosure does not imply the same example embodiment, but is provided to emphasize and explain different unique features. Additionally, the example embodiments presented above do not preclude implementation through combinations of features with other example embodiments. For example, even if matters described in a particular example embodiment are not described in other example embodiments, these matters may be understood to be relevant to other example embodiments unless there is a description in other example embodiments that contradicts or contradicts the stated matters.
[0091] In this disclosure, "connection" is a concept that includes not only direct connections but also indirect connections such as those via adhesive layers. Furthermore, "electrical connection" is a concept that includes both physical and non-physical connections. Additionally, expressions such as "first" and "second" are used to distinguish one component from another and do not limit the order and / or importance of the components. In some cases, without departing from the scope of the claims, a first component may be referred to as a second component, or similarly, a second component may be referred to as a first component.
Claims
1. A multilayer electronic component, comprising: The main body includes a dielectric layer and internal electrodes alternately disposed with the dielectric layer, wherein the dielectric layer includes Ba, Ti and Ge; as well as External electrodes are disposed on the main body. The dielectric layer includes a plurality of dielectric grains and grain boundaries disposed between adjacent dielectric grains. The average Ge content relative to Ti at the grain boundaries is greater than or equal to 0.2 at% and less than or equal to 4.5 at%.
2. The multilayer electronic component according to claim 1, wherein, The internal electrode comprises a Ni-Ge alloy.
3. The multilayer electronic component according to claim 2, wherein, The average Ge content relative to Ni in the internal electrode is greater than or equal to 0.32 at% and less than or equal to 6.3 at%.
4. The multilayer electronic component according to claim 1, wherein, The average Ge content, expressed as an atomic percentage relative to Ti, within the plurality of dielectric grains is less than the average Ge content, expressed as an atomic percentage relative to Ti, at the grain boundaries.
5. The multilayer electronic component according to claim 1, wherein, The main components of the dielectric layer include perovskite-type compounds represented by ABO3. Where A includes Ba, and B includes Ti.
6. The multilayer electronic assembly according to claim 1, wherein, The dielectric layer further includes one or more selected from the group consisting of Y, Dy, Tb, Ho, Er, Gd, Ce, Nd, Sm, Tm, La and Yb.
7. The multilayer electronic assembly according to claim 1, wherein, The dielectric layer further includes one or more elements selected from the group consisting of Mn, V, Cr, Fe, Co, Ni, Cu, and Zn.
8. The multilayer electronic component according to claim 1, wherein, The dielectric layer also includes Mg.
9. The multilayer electronic assembly according to claim 1, wherein, The dielectric layer further includes at least one selected from the group consisting of Si and Al.
10. The multilayer electronic assembly according to claim 1, wherein, The average Si content at the grain boundary, expressed as an atomic percentage relative to Ti, is greater than the average Ge content at the grain boundary, expressed as an atomic percentage relative to Ti.
11. The multilayer electronic assembly according to claim 1, wherein, The average Al content at the grain boundary, expressed as an atomic percentage relative to Ti, is greater than the average Ge content at the grain boundary, expressed as an atomic percentage relative to Ti.
12. The multilayer electronic assembly according to claim 1, wherein, The average Dy content relative to Ti at the grain boundaries is greater than or equal to 2.0 at% and less than or equal to 5.0 at%.
13. The multilayer electronic assembly according to claim 1, wherein, The average Mg content relative to Ti at the grain boundaries is greater than or equal to 0.2 at% and less than or equal to 1.0 at%.
14. The multilayer electronic assembly according to claim 1, wherein, The average size of the plurality of dielectric grains is greater than or equal to 120 nm and less than or equal to 200 nm.
15. A method for manufacturing a multilayer electronic component according to any one of claims 1-14, comprising: The slurry is coated onto the membrane to form multiple ceramic green sheets; The first paste is applied to each of the plurality of ceramic green sheets; The plurality of ceramic green sheets are stacked to form a laminate; The laminate is sintered to form the body. as well as The second paste is applied to the body to form the external electrode. The first paste or the slurry includes GeO2.
16. The method according to claim 15, wherein, The first paste contains GeO2.
17. The method according to claim 16, wherein, The first paste also includes Ni, and the Ge content relative to Ni is greater than or equal to 0.5 wt% and less than or equal to 10 wt%.
18. The method according to claim 15, wherein, The slurry includes GeO2.
Citation Information
Patent Citations
Mobile device holder
KR1020250043310A